Modelling of Atomic Imaging and Evaporation in the Field Ion Microscope - BOLAND, JOHN (My University, 2011)
Imaging and evaporation of atoms in the field ion microscope (FIM) has been modelled by using finite difference methods to calculate the voltage distribution around a tip and hence the electric field strength experienced by individual atoms. Atoms are evaporated based on field strength using a number of different mathematical models which yield broadly similar results. The tip shapes and simulated FIM images produced show strong agreement with experimental results for tips of the same orientation and crystal structure. Calculations have also been made to estimate the effects on resolution of using a field-sharpened tip for scanning probe microscopy.
PUBLISHED
Article ID 961239
Keywords: Atomic, molecular and chemical physics; Atomic Imaging; Nanoscience & Materials